What the pulmonary specialist should know about the new inhalation therapies - Laube, B L; Janssens, H M; de Jongh, F H C; Devadason, S G; Dhand, R; Diot, P; Everard, M L; Horvath, I; Navalesi, P; Voshaar, T; Chrystyn, H (The European respiratory journal, 2011)
A collaboration of multidisciplinary experts on the delivery of pharmaceutical aerosols was facilitated by the European Respiratory Society (ERS) and the International Society for Aerosols in Medicine (ISAM), in order to draw up a consensus statement with clear, up-to-date recommendations that enable the pulmonary physician to choose the type of aerosol delivery device that is most suitable for their patient. The focus of the consensus statement is the patient-use aspect of the aerosol delivery devices that are currently available. The subject was divided into different topics, which were in turn assigned to at least two experts. The authors searched the literature according to their own strategies, with no central literature review being performed. To achieve consensus, draft reports and recommendations were reviewed and voted on by the entire panel. Specific recommendations for use of the devices can be found throughout the statement. Healthcare providers should ensure that their patients can and will use these devices correctly. This requires that the clinician: is aware of the devices that are currently available to deliver the prescribed drugs; knows the various techniques that are appropriate for each device; is able to evaluate the patient's inhalation technique to be sure they are using the devices properly; and ensures that the inhalation method is appropriate for each patient.